Initial experience of percutaneous left atrial appendage closure using the LAmbre device for thromboembolic prevention. Issue 9 (September 2018) - Reinsch, Nico; Ruprecht, Ute; Buchholz, Jochen; Edel, Christoph; Kälsch, Hagen; Neven, Kars
Abstract : Aims: Stroke due to atrial fibrillation has been associated with a high risk of disability and mortality. Percutaneous left atrial appendage (LAA) closure has been established as an alternative strategy for stroke prevention in patients not eligible for oral anticoagulation. The LAmbre is a novel occluder, specifically designed for LAA closure adaptive to various LAA anatomies. The aim of this study was to demonstrate feasibility and initial experience in a nonprescreened patient cohort for LAA occlusion using the novel LAmbre occluder. Methods: The device was implanted in 11 patients with nonvalvular atrial fibrillation. Follow-up included transesophageal echocardiography and an outpatient visit at 6 weeks and 6 months after implantation. Results: All devices were implanted successfully. Device sizes ranged from 16/22 to 22/34 mm. Patients' mean CHA2 DS2 -VASc and HAS-BLED scores were 3.3 ± 1.0 and 3.2 ± 1.0, respectively. Two out of 11 patients had previously been rejected for Watchman occluder implantation by reasons of too small LAA. At 6 weeks and 6 months, there were no deaths, strokes, systemic thromboembolism or severe bleeding complications. There was no device-related thrombus or pericardial effusion seen with transesophageal echocardiography. In one out of 11 patients, a minimal peridevice flow (less than 5 mm) was present at 6-week follow-up. Conclusion: The LAmbre occluder is a novel LAA-closure device with features that provide many options for LAA-closure to physicians, particularly in patients with challenging anatomies. From our initial experience, implantation is associated with a good success rate and clinical outcome.